2013
DOI: 10.1155/2013/646728
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 Downregulates LPS-Induced NF-κB Activation through Inhibition of TAK1 Phosphorylation in RAW 264.7 Murine Macrophage

Abstract: The present study was carried out to evaluate the inhibitory effects of ginsenoside Rh2 on nuclear-factor- (NF-) κB in lipopolysaccharide- (LPS-) activated RAW 264.7 murine macrophages. RAW 264.7 cells were pretreated with indicated concentrations of ginsenoside Rh2 for 1 h prior to the incubation of LPS (1 μg/mL) for indicated time period. Ginsenoside Rh2 reduced CD14 and Toll-like receptor 4 (TLR4) expressions 24 h after LPS stimulation. Furthermore, ginsenoside Rh2 significantly inhibited TGF-beta-activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…Nuclear translocation, NF‐κB phosphorylation, and DNA binding are three important events in the final stage of NF‐κB pathway activation and have been shown to be inhibited by ginsenosides under various conditions. Nuclear translocation of NF‐κB p65 can be blocked by Rg1, 20( S )‐protopanaxatriol, Rh1, Rh2, Rb1, CK, Rg3, PF11, Rf, Rd, and Rb3 . The phosphorylation of NF‐κB p65 was found to be inhibited by Rg1, Rg3, and Ro .…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 93%
See 2 more Smart Citations
“…Nuclear translocation, NF‐κB phosphorylation, and DNA binding are three important events in the final stage of NF‐κB pathway activation and have been shown to be inhibited by ginsenosides under various conditions. Nuclear translocation of NF‐κB p65 can be blocked by Rg1, 20( S )‐protopanaxatriol, Rh1, Rh2, Rb1, CK, Rg3, PF11, Rf, Rd, and Rb3 . The phosphorylation of NF‐κB p65 was found to be inhibited by Rg1, Rg3, and Ro .…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 93%
“…Activated NF‐κB eventually binds to κB elements in the promoter region of target genes and initiates the transcriptional process of numerous genes . Recent investigations have demonstrated that the NF‐κB pathway is suppressed by a large number of ginsenosides, including Rg1, Rh2, Rb1, Compound K (CK), Rg3, Rb3, Rd, Pseudoginsenoside‐F11 (PF11), Re, Rh1, Rf, 20( S )‐protopanaxatriol, and Ro (Fig. ).…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Egfl7 and HIF-1a expression were determined using the SYBR Green Quantitect PCR Kit (Qiagen, Limburg, the Netherlands). The Egfl7 forward primer is 5'-TGCGACG-GACACAGA GCCTGCA-3' and the reverse primer is 5'-CAAGTATCTCCCTGCCATCCCA-3' [14,15]. The HIF-1a forward primer is CTCGGCGAA GCAAAGAGT and the reverse primer is GCCATCTA GGGCTTTCAG.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…By prompting the release of these inflammatory mediators, LPS not only activates both innate and adaptive immune responses at distal sites from the infection but also, in many cases, causes shock and death (11). Consequently, strategies that include prevention of ligand binding to TLR4 (12), blocking the interactions of TLR4 and adaptors in signaling pathways (13), and suppressing NF-B signaling pathways (14) have been reported to be effective in intervening in the development of experimental sepsis.…”
mentioning
confidence: 99%